Maxillofacial fibrous dysplasia - Mahajan Sumita; Kamboj Mala; Baoz Karen (Wolters Kluwer Medknow Publications, 2005)
Fibrous dysplasia is a non- neoplastic hamartomatous developmental fibro osseous lesion of bone. This paper provides a brief overview of fibrous dysplasia in a historic perspective and highlights the controversies in fibrous dysplasia seen in the cranio- maxillofacial lesions. A case report of a young woman is presented who was diagnosed as having maxillofacial fibrous dysplasia, thereby making an attempt to use this term in cases with relatively limited facial bone disease.